Integrating blockchain technology into the circular economy - Khan, Syed Abdul Rehman (IGI Global, 2022)
"This book of contributed chapters focuses on the potential role of industry in reducing environmental burdens throughout the product life cycle from the extraction of raw materials, to the production of goods, to the use of those goods and to the management of the resulting wastes discussing how the integration of blockchain technology in the idea of sustainability and waste management techniques improve the field of Industrial ecology